2022
DOI: 10.1111/1475-6773.13987
|View full text |Cite
|
Sign up to set email alerts
|

Does preventive dental care reduce nonpreventive dental visits and expenditures among Medicaid‐enrolled adults?

Abstract: Objective: To determine whether preventive dental visits are associated with fewer subsequent nonpreventive dental visits and lower dental expenditures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Regular dental visits contribute to the early detection of oral diseases, and continuous preventive care by dental professionals is effective in maintaining and improving oral health. Previous studies reported that preventive dental visits reduce future non-preventive dental care 7 and dental expenditures 7,8 . This suggests that health policy should prioritize frequent dental visits to improve people's health.…”
Section: Introductionmentioning
confidence: 98%
“…Regular dental visits contribute to the early detection of oral diseases, and continuous preventive care by dental professionals is effective in maintaining and improving oral health. Previous studies reported that preventive dental visits reduce future non-preventive dental care 7 and dental expenditures 7,8 . This suggests that health policy should prioritize frequent dental visits to improve people's health.…”
Section: Introductionmentioning
confidence: 98%
“…Timely dental care services, either for preventive care or necessary interventions, are imperative for good oral health [1,2]. Oral health can be viewed as a window into the overall health and health history, as evidenced by tooth loss, chronic periodontitis, and oral cancer [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%